2021
DOI: 10.1186/s12866-021-02185-3
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with surfactants enables quantification of translational activity by O-propargyl-puromycin labelling in yeast

Abstract: Background Translation is an important point of regulation in protein synthesis. However, there is a limited number of methods available to measure global translation activity in yeast. Recently, O-propargyl-puromycin (OPP) labelling has been established for mammalian cells, but unmodified yeasts are unsusceptible to puromycin. Results We could increase susceptibility by using a Komagataella phaffii strain with an impaired ergosterol pathway (erg6Δ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
(28 reference statements)
1
2
0
Order By: Relevance
“…Here we took advantage of the puromycin-based assay, which is an affordable non-radioactive system for protein labeling, to evaluate directly in vivo translation rate in Npa3 mutant cells. Previous studies suggest that specific S. cerevisiae strains are amenable to puromycin-based assays [68,69]. In this study, we demonstrated that, in our specific conditions, the puromycin system employed to directly assess translation in yeast is functional (Fig.…”
Section: Discussionsupporting
confidence: 53%
“…Here we took advantage of the puromycin-based assay, which is an affordable non-radioactive system for protein labeling, to evaluate directly in vivo translation rate in Npa3 mutant cells. Previous studies suggest that specific S. cerevisiae strains are amenable to puromycin-based assays [68,69]. In this study, we demonstrated that, in our specific conditions, the puromycin system employed to directly assess translation in yeast is functional (Fig.…”
Section: Discussionsupporting
confidence: 53%
“…A possible explanation for higher secretion rates in methanol conditions would be that growth on this carbon source is natively accompanied by very high expression of methanol utilization genes such as Aox1 [ 59 ], and methanol-grown cultures might therefore generally sustain high translation activity. However, in a recent study, translation activity at intermediate growth rates was comparable between methanol and glucose-limited conditions [ 60 ]. Another explanation would be that expression of the recombinant gene remained higher in the P AOX1 -based system, which, however, would be very difficult to compare directly.…”
Section: Discussionmentioning
confidence: 99%
“…OPP is a puromycin analog that enters the ribosome acceptor site and is incorporated into nascent polypeptides. This modification can be fluorescently labeled to mark sites of translation within the cell 50 . RPE-1 cells were S phase arrested, induced for Plk4 overexpression for 16 hours, labeled with OPP, and co-stained with Cep131.…”
Section: Centriolar Satellites and Unk Promote Local Translation At A...mentioning
confidence: 99%